Super-hydrophobic material as well as preparation method and application thereof

By using a combination of pH-responsive polymer solution and hydrophobic nanoparticles on cellulose fiber materials, the problem of complex preparation and slow response speed of conventional pH-responsive superhydrophobic materials is solved, and rapid response and self-repair performance are achieved, improving the performance of rapid response and self-repair The durability and application breadth of the material.

CN119264360AActive Publication Date: 2025-01-07JIANGNAN UNIV
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411509521.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-28
Publication Date
2025-01-07
Estimated Expiration
2044-10-28

AI Technical Summary

Technical Problem

The preparation process of conventional pH-responsive superhydrophobic materials is complex, with a long reaction period, slow response speed, short service life, and lack of self-healing performance.

Method used

Prepolymerization is carried out using diisocyanate compounds and bis(3-aminopropyl)-terminated poly(dimethylsiloxane), and addition of polyamino compounds containing tertiary amino groups are added for addition polymerization to form a pH-responsive polymer solution. , and hydrophobic nanoparticles are added thereto, and the cellulose fiber material is processed to prepare a pH-responsive and self-healing superhydrophobic material.

Benefits of technology

It realizes superhydrophobicity and underwater superoleophobicity that respond quickly in different pH environments, while also imparting the materials with resistance to organic solvents, friction loss, ultraviolet rays, heat resistance and other properties, extending their service life and having self-healing capabilities.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119264360A_ABST
    Figure CN119264360A_ABST
Patent Text Reader

Abstract

The invention discloses a super-hydrophobic material as well as a preparation method and application thereof, and belongs to the field of functional materials. The preparation method comprises the following steps: firstly, dissolving bis (3-aminopropyl) terminated poly (dimethyl siloxane) and a diisocyanate compound in an organic solvent, carrying out prepolymerization, then slowly adding a polyamino compound of tertiary amino, and carrying out addition polymerization reaction to obtain a pH response type polymer solution; then, hydrophobic nanoparticles are added into the pH response type polymer solution, and a mixed solution is obtained; finally, the mixed solution is used for treating a cellulose fiber material, and the pH-responsive and self-repairing super-hydrophobic material is obtained. According to the invention, protonation and deprotonation of the pH-responsive polymer in different pH environments are utilized to provide super hydrophobicity and underwater super oleophobicity for the surface of the super-hydrophobic material, and the pH-responsive super-hydrophobic material has the properties of organic solvent resistance, wear resistance, ultraviolet resistance, heat resistance and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a super-hydrophobic material and a preparation method and application thereof, belonging to the field of functional materials. Background Art

[0002] Superhydrophobicity refers to a wetting state where the contact angle of water on the surface is greater than 150°. When the contact angle of the material surface to water exceeds 150°, it is called a superhydrophobic surface. There are many superhydrophobic phenomena in nature, such as the surface of plants such as lotus leaves, the wings of insects such as butterflies, etc. Water droplets can roll freely on the superhydrophobic surface and take away the pollutants attached to the superhydrophobic surface, achieving a self-cleaning effect. Superhydrophobic surfaces are widely used in various fields such as anti-fouling, self-cleaning, anti-icing, anti-corrosion, water-oil separation, etc. due to their special surface properties. Inspired by natural lotus leaves, researchers have realized that the coexistence of wax and microscale is the key to achieving superhydrophobic surfaces, that is, materials with low surface energy and micro-nanostructures can be used to create superhydrophobic surfaces. A single wettability limits the ability of materials to handle complex practical scenarios, so it is necessary to design and prepare materials with fast and adjustable wettability.

[0003] Cellulose fiber materials are the most widely used natural fiber fabrics due to their low price, soft feel, good moisture absorption and breathability. Because the cellulose surface contains a large number of hydroxyl groups, it is highly hydrophilic and easy to dye, but it also brings a lot of problems, such as being difficult to clean due to stains, being prone to mildew, and breeding bacteria. These problems have greatly limited the application of cellulose fiber materials. Attaching a layer of super-hydrophobic coating to the surface of cellulose fiber materials can give cellulose fiber materials a self-cleaning effect, greatly improving the problems of easy contamination and mildew, but the single wettability limits the material's ability to handle complex practical scenarios.

[0004] Currently, there are many literatures mentioning the preparation of pH-responsive superhydrophobic materials;

[0005] For example: CN112981973A discloses a method for preparing a pH-responsive super-hydrophobic material, which comprises the steps of uniformly mixing super-hydrophobic silica and acrylate copolymer and spraying the mixture onto a fabric substrate to obtain a pH-responsive super-hydrophobic coating; realizing super-hydrophobic-hydrophilic conversion of super-hydrophobic materials within a certain pH range, having good environmental responsiveness, good wear resistance, strong adhesion, and good adaptability to substrates, overcoming the weaknesses of traditional water-oil separation methods that are complex and time-consuming to operate, and simplifying the post-processing process required for super-hydrophobic-super-oleophilic materials from the perspective of separating the water phase, and the preparation process is simple and easy to control;

[0006] CN113463402A discloses a method for preparing a pH-responsive super-hydrophobic-hydrophilic reversible transformation material surface, which comprises first preparing microcapsules, then adding fluorine-containing substances to form pH-responsive microcapsules, and finally using the microcapsules on the material surface to form a pH-responsive super-hydrophobic-hydrophilic reversible transformation material surface; the method can realize reversible transformation from super-hydrophobic to hydrophilic, and the number of transformations can reach dozens of times, and the method has strong durability and the ability to resist damage from the external environment; however, when a droplet of pH=1 is placed on the hydrophobic surface, the droplet is completely absorbed after 120s, and the response speed is slow.

[0007] Moreover, pyridine, carboxyl and tertiary amine groups are typical pH-responsive functional groups. The carboxyl group can be protonated at low pH values, showing relatively hydrophobic properties, while at high pH values, it appears in the form of carboxylate anions, which have relatively hydrophilic properties. However, compared with tertiary amine groups, carboxyl groups are easily involved in chemical reactions such as esterification and amidation, which affects their stability in applications. The protonation and deprotonation process of pyridine is not as significant as that of tertiary amine groups, resulting in weaker responsiveness and slow response speed. In addition, the introduction of pyridine functional groups into materials usually requires multiple chemical reactions, which increases the complexity and cost of material synthesis.

[0008] It can be seen that the preparation process of conventional pH-responsive superhydrophobic materials is complicated and the reaction cycle is long; the response speed is slow and the service life is short; in addition, it does not have self-healing properties; therefore, it is necessary to prepare superhydrophobic materials with fast response, adjustable wettability, self-healing and good durability. Summary of the invention

[0009] [Technical issues]

[0010] The preparation process of conventional pH-responsive superhydrophobic materials is complex, the reaction cycle is long, the response speed is slow, and the service life is short; in addition, they do not yet have self-healing properties.

[0011] [Technical solution]

[0012] In order to solve the above problems, the present invention first adopts diisocyanate compounds, bis (3-aminopropyl) end-capped poly (dimethylsiloxane) dissolved in an organic solvent, prepolymerized, and then slowly added with a polyamino compound containing a tertiary amino group, and subjected to addition polymerization to obtain a pH responsive polymer solution; afterwards, hydrophobic nanoparticles are added to the pH responsive polymer solution to obtain a mixed solution; finally, the mixed solution is used to treat cellulose fiber materials to obtain a pH responsive and self-repairing super-hydrophobic material. The present invention utilizes the protonation and deprotonation of pH responsive polymers in different pH environments, and provides super-hydrophobicity and underwater super-oleophobicity for the surface of super-hydrophobic materials, while enabling the pH responsive super-hydrophobic material to have resistance to organic solvents, wear resistance, UV resistance, heat resistance and other properties.

[0013] The first object of the present invention is to provide a method for preparing a pH responsive polymer solution, comprising the steps of:

[0014] Dissolving bis(3-aminopropyl)-terminated poly(dimethylsiloxane) and diisocyanate compounds in an organic solvent for prepolymerization, and then slowly adding a polyamino compound containing a tertiary amino group to carry out addition polymerization to obtain a pH-responsive polymer solution;

[0015] Wherein, the polyamino compound containing tertiary amino group is one or two of tris(2-aminoethyl)amine and laurylamine dipropylene diamine;

[0016] The molar ratio of the bis(3-aminopropyl)-terminated poly(dimethylsiloxane), the diisocyanate compound and the polyamino compound containing tertiary amino groups is 1-4:2-14:2-10.

[0017] In one embodiment of the present invention, the CAS code of bis(3-aminopropyl)-terminated poly(dimethylsiloxane) is 106214-84-0.

[0018] In one embodiment of the present invention, the diisocyanate compound is one or more of isophorone diisocyanate, toluene diisocyanate, and hexamethylene diisocyanate.

[0019] In one embodiment of the present invention, the molar ratio of the bis(3-aminopropyl)-terminated poly(dimethylsiloxane), the diisocyanate compound and the tertiary amino group-containing polyamino compound is 3:11:7.

[0020] In one embodiment of the present invention, the prepolymerization is carried out at 20-50° C. and 300-500 rpm for 1-10 hours; nitrogen purging is required for more than 20 minutes before the prepolymerization.

[0021] In one embodiment of the present invention, the organic solvent is one or more of tetrahydrofuran, chloroform and acetone.

[0022] In one embodiment of the present invention, the addition polymerization reaction can be carried out without adding a catalyst.

[0023] In one embodiment of the present invention, the addition polymerization reaction is carried out at 20-50° C. and 300-500 rpm for 1-10 h.

[0024] The second object of the present invention is the pH responsive polymer solution prepared by the method of the present invention.

[0025] In one embodiment of the present invention, the mass fraction of the pH responsive polymer in the pH responsive polymer solution is 5-25%.

[0026] In one embodiment of the present invention, the mass fraction of the pH responsive polymer in the pH responsive polymer solution is the percentage of the sum of the masses of the bis(3-aminopropyl)-terminated poly(dimethylsiloxane), the diisocyanate compound and the polyamino compound containing tertiary amino groups in the mass of the entire solution.

[0027] The third object of the present invention is to provide a method for preparing a pH-responsive and self-healing superhydrophobic material, comprising the following steps:

[0028] Hydrophobic nanoparticles are added to a pH-responsive polymer solution and mixed evenly to obtain a mixed solution; then, a cellulose fiber material is immersed in the mixed solution, taken out, and solidified to obtain a pH-responsive and self-healing superhydrophobic material.

[0029] In one embodiment of the present invention, the hydrophobic nanoparticles are one or more of titanium dioxide, silicon dioxide, and carbon black nanoparticles; and the particle size is 1-200 nm.

[0030] In one embodiment of the present invention, the mass concentration of the hydrophobic nanoparticles in the pH responsive polymer solution is 10-40%.

[0031] In one embodiment of the present invention, the uniform mixing is ultrasonic mixing; and the ultrasonic treatment is ultrasonic treatment at 200-400W for 5-20min.

[0032] In one embodiment of the present invention, the cellulose fiber material is one or more of cotton fabric, paper, viscose fabric, modal fabric or lyocell fabric; it can also be a blended fabric, such as a blended fabric of cotton, viscose, modal, lyocell, etc.

[0033] In one embodiment of the present invention, the cellulose fiber material needs to be pretreated before use, specifically:

[0034] The cellulose fiber material is ultrasonically treated with deionized water and ethanol in sequence, and washed in each solvent for 20 to 30 minutes. After washing, it is dried to obtain a pretreated cellulose fiber material.

[0035] In one embodiment of the present invention, the immersion is carried out at 20-30° C., and may be accompanied by ultrasound, wherein the ultrasound is carried out at 200-400 W for 5-20 min.

[0036] In one embodiment of the present invention, the curing is performed at 50-150° C. for 10-60 min.

[0037] The fourth objective of the present invention is a pH-responsive and self-healing superhydrophobic material prepared by the method described in the present invention.

[0038] The fifth objective of the present invention is to use the pH-responsive polymer solution and the pH-responsive and self-healing superhydrophobic material described in the present invention in the fields of anti-fouling, self-cleaning, anti-icing, anti-corrosion or water-oil separation.

[0039] A sixth object of the present invention is to provide an oil-water separation method, which uses the pH-responsive and self-healing superhydrophobic material described in the present invention.

[0040] The seventh object of the present invention is to provide a method for improving the pH response, superhydrophobicity and self-repairing properties of cotton fabrics, which uses the pH-responsive and self-repairing superhydrophobic material described in the present invention.

[0041] The eighth object of the present invention is to provide a method for quickly achieving reversible switching of superhydrophobic-hydrophilic-superhydrophobic on the surface of cotton fabrics, which uses the pH-responsive and self-healing superhydrophobic material described in the present invention.

[0042] [Beneficial Effects]

[0043] (1) The present invention introduces a bis(3-aminopropyl)-terminated poly(dimethylsiloxane) and a polyamino compound containing a tertiary amino group into the same molecule to obtain a pH-responsive superhydrophobic polymer; therefore, the polymer has both pH-responsive properties and low surface energy; wherein the tertiary amine structure can induce its protonation and deprotonation to change the surface wettability by changing the pH.

[0044] (2) The present invention combines the unique surface texture and structural characteristics of hydrophobic nanoparticles and cellulose fiber materials and their weaving methods to form a micro-nano multi-level structure, which further enhances the hydrophobicity and response performance of the coating.

[0045] (3) The method for preparing super-hydrophobic cellulose fiber materials of the present invention can prepare super-hydrophobic cellulose fiber materials with properties such as resistance to organic solvents, friction resistance, UV resistance, and heat resistance without the need for complex equipment or processes.

[0046] (4) After the present invention performs pH-responsive superhydrophobic finishing on the cellulose fiber material, the roughness is provided by the hydrophobic nanoparticles, and the bis(3-aminopropyl)-terminated poly(dimethylsiloxane) reduces the surface energy of the cellulose fiber material; a polyamino compound containing tertiary amino groups is introduced to provide pH-responsive performance through its protonation and deprotonation, thereby achieving rapid switching of wettability, and finally preparing a pH-responsive superhydrophobic cellulose fiber material with organic solvent resistance, abrasion resistance, UV resistance, heat resistance and the like. BRIEF DESCRIPTION OF THE DRAWINGS

[0047] Figure 1The reaction mechanism and infrared spectra of the prepolymer (PDMS-IPDI) and the product (pH-PU) in the pH-responsive polymer in Example 1 before the reaction.

[0048] Figure 2 The scanning electron microscope images (c: 10 μm; d: 1 μm) of the original cotton fabric (a), the hydrophobic cotton fabric prepared in Comparative Example 3 (b), and the super hydrophobic cotton fabric prepared in Example 4 are shown.

[0049] Figure 3 The present invention is a Fourier infrared transform spectrum diagram of the original cotton fabric, the pH responsive polymer, and the super-hydrophobic cotton fabric prepared in Example 4, an X-ray photoelectron spectrum diagram of the super-hydrophobic cotton fabric prepared in Example 4, and a C1s fitting curve diagram; wherein, (a) is a Fourier infrared transform spectrum diagram of the original cotton fabric, the pH responsive polymer, and the super-hydrophobic cotton fabric prepared in Example 4; (b) is an X-ray photoelectron spectrum diagram of the original cotton fabric and the super-hydrophobic cotton fabric prepared in Example 4; (c) is a C1s fitting curve diagram of the original cotton fabric; and (d) is a C1s fitting curve diagram of the super-hydrophobic cotton fabric prepared in Example 4.

[0050] Figure 4 The present invention is a schematic diagram, a water contact angle (WCA) and a SEM image of the superhydrophobic cotton fabric prepared in Example 4 after Martindale friction test, tape stripping and ultrasonic test; wherein, (1) is a schematic diagram, a WCA and a SEM image (a) of the superhydrophobic cotton fabric prepared in Example 4 after Martindale friction test; (2) is a schematic diagram, a WCA and a SEM image (b) of the superhydrophobic cotton fabric prepared in Example 4 after tape stripping; (3) is a schematic diagram, a WCA and a SEM image (c) of the superhydrophobic cotton fabric prepared in Example 4 after ultrasonic test.

[0051] Figure 5 The chemical stability performance test of the super-hydrophobic cotton fabric prepared in Example 4 is shown in FIG. 4; wherein, (a) is a graph showing the contact angle variation over time of the super-hydrophobic cotton fabric prepared in Example 4 in an oven at 150° C.; (b) is a graph showing the contact angle variation over time of the super-hydrophobic cotton fabric prepared in Example 4 after being treated in a sun-resistant weather tester; (c) is a graph showing the contact angle data after the fabric is immersed in solutions of different pH values ​​for 72 hours; and (d) is a graph showing the contact angle data after being immersed in organic solvents (tetrahydrofuran, ethanol, n-hexane, acetone, toluene) for 72 hours.

[0052] Figure 6 This is a self-healing performance test of the super-hydrophobic cotton fabric prepared in Example 4; wherein (a) is the test result of 5 plasma treatment-thermal repair cycles; and (b) is the self-healing mechanism of the super-hydrophobic cotton fabric.

[0053] Figure 7The super-hydrophobic cotton fabric prepared in Example 4 is used in the field of oil-water separation; wherein (a) is an oil removal model; (b) is a water removal model; (c) is an oil removal model after 5 cycles; (d) is a water removal model after 5 cycles. DETAILED DESCRIPTION

[0054] The preferred embodiments of the present invention are described below. It should be understood that the embodiments are for better explaining the present invention and are not used to limit the present invention.

[0055] Test method:

[0056] 1. Super hydrophobic performance test:

[0057] The static contact angle of the superhydrophobic cotton fabric was tested by measuring 5 μL water droplets at three different positions of the fabric using a DSA-25 contact angle meter, and then the average value was calculated.

[0058] 2. Friction resistance test:

[0059] According to GB / T 21196.4-2007 “Determination of the abrasion resistance of fabrics by the Martindale method Part 4: Assessment of changes in appearance”, the abrasion resistance of the modified cotton fabric was tested using a YG(B)401T Martindale abrasion tester.

[0060] 3. Tape peeling test:

[0061] For the tape peel test, a 200 g weight was placed on the tape (3M; Scotch Magic Tape 810) to apply pressure to the tape so that the tape could be in close and uniform contact with the super-hydrophobic cotton fabric. Afterwards, the tape was carefully removed and the contact angle of the super-hydrophobic cotton fabric was measured, once every 20 scratches.

[0062] 4. Ultrasonic testing:

[0063] The superhydrophobic cotton fabric was immersed in ethanol at room temperature and treated with ultrasound at a frequency of 28 kHz and a power of 300 W for 240 min. The contact angle was recorded every 60 min.

[0064] 5. High temperature resistance test:

[0065] The superhydrophobic cotton fabric was placed at 150 °C for 120 h, and the contact angle was measured every 20 h.

[0066] 6. Sunlight resistance test:

[0067] According to the test method of GB / T 8427-2009 “Textiles - Tests for colour fastness - Colour fastness to artificial light: Xenon arc lamp”, a xenon arc lamp was used as the light source, the super-hydrophobic cotton fabric was exposed to the sun for 60 hours, and the contact angle change was recorded every 10 hours.

[0068] 7. Organic solvent resistance test:

[0069] The superhydrophobic cotton fabrics were immersed in different organic solvents (acetone, ethanol, toluene, and n-hexane) for 72 hours, rinsed with water several times, and dried at 80°C for 30 minutes, and then the changes in contact angles were detected.

[0070] 8. Self-repair performance test:

[0071] The superhydrophobic cotton fabric was treated with a plasma cleaner (SUNJUNE PLASMAVP-R3, China) under high vacuum conditions for 30 s to achieve a superhydrophilic state. Subsequently, the plasma-treated samples were cured under ambient conditions or in an oven at 120 °C to restore their superhydrophobicity, and their contact angles were measured.

[0072] The raw materials used in the examples are:

[0073] Bis(3-aminopropyl) terminated poly(dimethylsiloxane): CAS code is 106214-84-0;

[0074] Isophorone diisocyanate: CAS code is 4098-71-9;

[0075] Laurylamine dipropylene diamine: CAS code is 2372-82-9;

[0076] Silica nanoparticles: particle size 16 nm, purchased from Shandong Yousuo Chemical Technology Co., Ltd.;

[0077] Cotton fabric: twill, the linear density of warp and weft yarns are both 18.4tex, and the warp and weft densities are 250 strands / 10cm and 150 strands / 10cm respectively).

[0078] The cotton fabrics used in the examples and comparative examples were all pretreated. The pretreatment was to ultrasonically treat the cotton fabrics with deionized water and ethanol in sequence, wash them in each solvent for 20 minutes, take them out after washing and dry them in an oven at 80°C.

[0079] Example 1

[0080] A method for preparing a pH responsive polymer solution comprises the following steps:

[0081] 1.5 g of bis(3-aminopropyl)-terminated poly(dimethylsiloxane) (NH2-PDMS-NH2) and 0.489 g of isophorone diisocyanate (IPDI) were dissolved in 13.651 g of tetrahydrofuran, purged with nitrogen for 30 min, and then prepolymerized at 25°C and 500 rpm for 2 h. Then, 0.42 g of laurylamine dipropylene diamine was slowly added dropwise thereto, and addition polymerization reaction was carried out at 25°C and 500 rpm for 4 h to obtain a pH-responsive polymer solution; wherein the mass fraction of the pH-responsive polymer in the pH-responsive polymer solution was 15%; the molar ratio of bis(3-aminopropyl)-terminated poly(dimethylsiloxane), isophorone diisocyanate, and laurylamine dipropylene diamine was 3:11:7.

[0082] Its reaction mechanism diagram and infrared spectrum are shown in Figure 1 .

[0083] from Figure 1 It can be seen that: 1700cm -1 The appearance of the urea bond group absorption peaks at the left and right sides confirmed the successful synthesis of the PDMS-IPDI prepolymer; after the reaction of laurylamine dipropylene diamine with the PDMS-IPDI prepolymer, 2250cm -1 The characteristic peaks of the isocyanate group on the left and right sides basically disappeared, indicating that the laurylamine dipropylene diamine successfully reacted with the prepolymer. These evidences prove that pH-PU has been successfully synthesized. -1 The absorption peak of Si-CH3 rocking vibration is at 1000cm -1 It is the stretching peak of silicon-oxygen-silicon; 1260cm -1 is the symmetrical bending absorption peak of Si-CH3, 3000cm -1 On the left and right are the characteristic peaks of stretching vibration of methyl and methylene.

[0084] Example 2

[0085] A method for preparing a pH-responsive and self-healing superhydrophobic material comprises the following steps:

[0086] 0.1 g of silica nanoparticles were added to 4 g of the pH-responsive polymer solution of Example 1, and the mixture was uniformly mixed by ultrasonic treatment at a frequency of 28 kHz and a power of 300 W for 10 min to obtain a mixed solution;

[0087] The cotton fabric was immersed in the mixed solution at 25°C, accompanied by ultrasonic treatment at a frequency of 28 kHz and a power of 300 W for 5 min, taken out, and thermally cured at 120°C for 30 min to obtain a pH-responsive and self-healing superhydrophobic material.

[0088] Example 3

[0089] The amount of the silicon dioxide nanoparticles in Example 2 was adjusted to 0.2 g, and the other ingredients were kept consistent with Example 2 to obtain a super hydrophobic material.

[0090] Example 4

[0091] The amount of silicon dioxide nanoparticles in Example 2 was adjusted to 0.3 g, and the other ingredients were kept consistent with Example 2 to obtain a super hydrophobic material.

[0092] Example 5

[0093] The amount of silicon dioxide nanoparticles in Example 2 was adjusted to 0.4 g, and the other ingredients were kept consistent with Example 2 to obtain a super hydrophobic material.

[0094] Example 6

[0095] The preparation method of the pH responsive polymer solution in Example 2 is adjusted as follows:

[0096] 1.5g of bis(3-aminopropyl)-terminated poly(dimethylsiloxane) (NH2-PDMS-NH2) and 0.60g of isophorone diisocyanate (IPDI) were dissolved in 13.06g of tetrahydrofuran, purged with nitrogen for 30min, prepolymerized at 25°C and 500rpm for 2h, and then 0.205g of tri(2-aminoethyl)amine was slowly added dropwise thereto, and addition polymerization was carried out at 25°C and 500rpm for 4h to obtain a pH-responsive polymer solution; wherein the mass fraction of the pH-responsive polymer in the pH-responsive polymer solution was 15%; the molar ratio of bis(3-aminopropyl)-terminated poly(dimethylsiloxane), isophorone diisocyanate, and tri(2-aminoethyl)amine was 3:13.5:7;

[0097] The other steps were the same as those in Example 2 to obtain a super hydrophobic material.

[0098] Example 7

[0099] The amount of tetrahydrofuran in Example 1 was adjusted to 21.681 g, and the other contents were kept the same as in Example 1, to obtain a pH-responsive polymer solution having a mass fraction of 10% of the pH-responsive polymer;

[0100] The mass fraction of the pH-responsive polymer in the pH-responsive polymer solution in Example 2 was adjusted to 10%, and the other contents were kept the same as in Example 2 to obtain a superhydrophobic material.

[0101] Example 8

[0102] The amount of tetrahydrofuran in Example 1 was adjusted to 9.636 g, and the other contents were kept the same as in Example 1, to obtain a pH-responsive polymer solution having a mass fraction of the pH-responsive polymer of 20%;

[0103] The mass fraction of the pH-responsive polymer in the pH-responsive polymer solution in Example 2 was adjusted to 20%, and the other contents were kept consistent with Example 2 to obtain a superhydrophobic material.

[0104] Comparative Example 1

[0105] The preparation method of the pH responsive polymer solution in adjustment Example 2 is as follows:

[0106] 0.5 g of bis(3-aminopropyl)-terminated poly(dimethylsiloxane) and 0.489 g of isophorone diisocyanate were dissolved in 8.66 g of tetrahydrofuran, purged with nitrogen for 30 min, prepolymerized at 25°C and 500 rpm for 2 h, and then 0.54 g of laurylamine dipropylene diamine was slowly added dropwise thereto, and an addition polymerization reaction was carried out at 25°C and 500 rpm for 4 h to obtain a pH-responsive polymer solution; wherein the mass fraction of the pH-responsive polymer in the pH-responsive polymer solution was 15%; the molar ratio of bis(3-aminopropyl)-terminated poly(dimethylsiloxane), isophorone diisocyanate, and laurylamine dipropylene diamine was 1:11:9;

[0107] At the same time, the amount of silicon dioxide nanoparticles was adjusted to 0 g, that is, the addition of silicon dioxide nanoparticles was omitted, and the other conditions were kept consistent with Example 2 to obtain a super hydrophobic material.

[0108] Comparative Example 2

[0109] The preparation method of the pH responsive polymer solution in adjustment Example 2 is as follows:

[0110] 1.0 g of bis(3-aminopropyl)-terminated poly(dimethylsiloxane) and 0.489 g of isophorone diisocyanate were dissolved in 11.16 g of tetrahydrofuran, purged with nitrogen for 30 min, and prepolymerized at 25°C and 500 rpm for 2 h, and then 0.48 g of laurylamine dipropylene diamine was slowly added dropwise thereto, and an addition polymerization reaction was carried out at 25°C and 500 rpm for 4 h to obtain a pH-responsive polymer solution; wherein the molar ratio of bis(3-aminopropyl)-terminated poly(dimethylsiloxane), isophorone diisocyanate, and laurylamine dipropylene diamine was 2:11:8;

[0111] At the same time, the amount of silicon dioxide nanoparticles was adjusted to 0 g, that is, the addition of silicon dioxide nanoparticles was omitted, and the other conditions were kept consistent with Example 2 to obtain a super hydrophobic material.

[0112] Comparative Example 3

[0113] The preparation method of the pH responsive polymer solution in adjustment Example 2 is as follows:

[0114] 1.5 g of bis(3-aminopropyl)-terminated poly(dimethylsiloxane) and 0.489 g of isophorone diisocyanate were dissolved in 8.66 g of tetrahydrofuran, purged with nitrogen for 30 min, and prepolymerized at 25° C. and 500 rpm for 2 h, and then 0.42 g of laurylamine dipropylene diamine was slowly added dropwise thereto, and an addition polymerization reaction was carried out at 25° C. and 500 rpm for 4 h to obtain a pH-responsive polymer solution; wherein the molar ratio of bis(3-aminopropyl)-terminated poly(dimethylsiloxane), isophorone diisocyanate, and laurylamine dipropylene diamine was 3:11:7;

[0115] At the same time, the amount of silicon dioxide nanoparticles was adjusted to 0 g, that is, the addition of silicon dioxide nanoparticles was omitted, and the other conditions were kept consistent with Example 2 to obtain a super hydrophobic material.

[0116] Comparative Example 4

[0117] The preparation method of the pH responsive polymer solution in adjustment Example 2 is as follows:

[0118] 2.0 g of bis(3-aminopropyl)-terminated poly(dimethylsiloxane) and 0.489 g of isophorone diisocyanate were dissolved in 8.66 g of tetrahydrofuran, purged with nitrogen for 30 min, and prepolymerized at 25° C. and 500 rpm for 2 h, and then 0.36 g of laurylamine dipropylene diamine was slowly added dropwise thereto, and an addition polymerization reaction was carried out at 25° C. and 500 rpm for 4 h to obtain a pH-responsive polymer solution; wherein the molar ratio of bis(3-aminopropyl)-terminated poly(dimethylsiloxane), isophorone diisocyanate, and laurylamine dipropylene diamine was 4:11:6;

[0119] At the same time, the amount of silicon dioxide nanoparticles was adjusted to 0 g, that is, the addition of silicon dioxide nanoparticles was omitted, and the other conditions were kept consistent with Example 2 to obtain a super hydrophobic material.

[0120] Comparative Example 5

[0121] The preparation method of the pH responsive polymer solution in adjustment Example 2 is as follows:

[0122] 2.5 g of bis(3-aminopropyl)-terminated poly(dimethylsiloxane) and 0.489 g of isophorone diisocyanate were dissolved in 8.66 g of tetrahydrofuran, purged with nitrogen for 30 min, and then prepolymerized at 25°C and 500 rpm for 2 h. Then, 0.30 g of laurylamine dipropylene diamine was slowly added dropwise thereto, and an addition polymerization reaction was carried out at 25°C and 500 rpm for 4 h to obtain a pH-responsive polymer solution; wherein the molar ratio of bis(3-aminopropyl)-terminated poly(dimethylsiloxane), isophorone diisocyanate, and laurylamine dipropylene diamine was 5:11:5.

[0123] At the same time, the amount of silicon dioxide nanoparticles was adjusted to 0 g, that is, the addition of silicon dioxide nanoparticles was omitted, and the other conditions were kept consistent with Example 2 to obtain a super hydrophobic material.

[0124] The obtained super hydrophobic material was subjected to performance testing, and the test results are as follows:

[0125] Table 1

[0126]

[0127] Note: The wettability switching time is the time taken for a water drop to completely wet the fabric after it contacts the fabric by recording a video using a contact angle tester.

[0128] As can be seen from Table 1, hydrophobic nanoparticles can improve surface roughness, which is crucial to achieving super-hydrophobicity. When the content of hydrophobic nanoparticles is low, most of the added hydrophobic nanoparticles may be coated by the responsive polymer, so that the best effect cannot be achieved. When the content of hydrophobic nanoparticles is high, too much silica destroys the optimal equilibrium state between the polymer and the hydrophobic nanoparticles. Therefore, although the initial contact angle is relatively high, the mechanical durability decreases. In Example 4, the content of silica nanoparticles is the most appropriate, which can improve the surface roughness and have the best mechanical durability. Further stability research is conducted on Example 4.

[0129] Figure 3 The Fourier infrared transform spectra of the original cotton fabric, the pH responsive polymer, and the superhydrophobic cotton fabric prepared in Example 4, the X-ray photoelectron spectrum of the superhydrophobic cotton fabric prepared in Example 4, and the C1s fitting curve diagram; wherein, (a) is the Fourier infrared transform spectra of the original cotton fabric, the pH responsive polymer, and the superhydrophobic cotton fabric prepared in Example 4; (b) is the X-ray photoelectron spectrum of the original cotton fabric and the superhydrophobic cotton fabric prepared in Example 4; (c) is the C1s fitting curve diagram of the original cotton fabric; (d) is the C1s fitting curve diagram of the superhydrophobic cotton fabric prepared in Example 4. Figure 3 As can be seen from (a), the super hydrophobic cotton fabric is better than the original cotton at 800 cm -1 A new absorption peak appears at 1260 cm, which is the swing vibration absorption peak of Si-CH3. -1 The symmetrical bending absorption peak of Si-CH3 is 1700 cm-1, which is higher than that of the original cotton. -1 There are urea bond group absorption peaks on the left and right, as well as 3000cm -1 The obvious enlargement of the stretching vibration characteristic peaks of the left and right methyl and methylene groups is caused by the combination of pH-responsive polymer and cotton fabric. Figure 3 As can be seen in (b), compared with the original cotton fabric, two new elements, N and Si, were detected in the super-hydrophobic cotton fabric. Figure 3It can be seen from (c) and (d) that the CH / CC bond is at 284.8 eV, the COC bond is at 286.42 eV, and the C=O bond is at 288.09 eV; the C1s spectrum of the original cotton fabric is fitted with 3 peaks, while the C1s spectrum of the superhydrophobic cotton fabric is fitted with 5 peaks, and two new peaks of the CN bond at 286.0 eV and the C-Si bond at 283.9 eV are detected. These two peaks belong to the pH-responsive polymer.

[0130] Figure 4 Schematic diagram, water contact angle (WCA) and SEM image of the super-hydrophobic cotton fabric prepared in Example 4 after Martindale friction test, tape stripping and ultrasonic test; wherein, (1) is a schematic diagram, WCA and SEM image (a) of the super-hydrophobic cotton fabric prepared in Example 4 after Martindale friction test; (2) is a schematic diagram, WCA and SEM image (b) of the super-hydrophobic cotton fabric prepared in Example 4 after tape stripping; (3) is a schematic diagram, WCA and SEM image (c) of the super-hydrophobic cotton fabric prepared in Example 4 after ultrasonic test. Figure 4 It can be seen that: as the experiment proceeds, the contact angle of the super-hydrophobic cotton fabric prepared in Example 4 gradually decreases, but the super-hydrophobicity is not lost after 700 Martindale friction tests, 100 tape tests, and 6 hours of ultrasound.

[0131] Figure 5 The chemical stability performance test of the super-hydrophobic cotton fabric prepared in Example 4; wherein, (a) is a graph showing the contact angle variation over time of the super-hydrophobic cotton fabric prepared in Example 4 in a 150°C oven; (b) is a graph showing the contact angle variation over time of the super-hydrophobic cotton fabric prepared in Example 4 after being treated in a sun-resistant weather tester; (c) is a graph showing the contact angle data after immersing the fabric in solutions of different pH values ​​for 72 hours; (d) is a graph showing the contact angle data after immersing the fabric in organic solvents (tetrahydrofuran, ethanol, n-hexane, acetone, toluene) for 72 hours. Figure 5 As shown in (a), the contact angle of the super-hydrophobic cotton fabric is not affected by the long-term high temperature environment, and the contact angle hardly changes. Figure 5 As shown in (b), after a long period of sunlight and weather resistance testing, the contact angle of the super-hydrophobic cotton fabric was not affected and the change in the contact angle was not obvious. Figure 5 As shown in (c), the contact angle of the super-hydrophobic cotton fabric did not change significantly after being immersed in an acidic solution, but the contact angle of the cotton fabric immersed in a strong alkaline solution decreased, but still maintained hydrophobicity. Figure 5 As shown in (d), the contact angle of the superhydrophobic cotton fabric did not change significantly after being immersed in an organic solvent.

[0132] Figure 6 This is a self-repairing test of the super hydrophobic cotton fabric prepared in Example 4. Figure 6 It can be seen that after 30s of plasma treatment, the superhydrophobic cotton fabric was transformed from superhydrophobic to superhydrophilic, and the WCA was directly reduced to 0°. After the superhydrophobic coating was damaged, it was heated at 120°C for 30min, and the coating could restore its superhydrophobicity, with the WCA reaching 157.0±0.5°. Even after 5 cycles of plasma treatment-thermal repair, the superhydrophobic cotton fabric was still able to restore its superhydrophobicity. During the plasma treatment, the hydrophobic PDMS chains on the coating surface were damaged, and hydrophilic oxygen-containing groups were introduced into the coating surface. After high-temperature treatment, the hydrophobic PDMS chains migrated back to the damaged area and covered the hydrophilic groups, realizing the self-healing process.

[0133] Example 9 Application of Oil-Water Separation

[0134] To further demonstrate the application of superhydrophobic cotton fabric in oil-water separation, various oils mixed with water can be separated using oil removal and water removal methods due to its wettability switching properties. In this case, gravity is the only driving force.

[0135] When separating water and heavy oil (oil removal model), take ethylene dichloride as an example.

[0136] The mixture of ethylene dichloride and water was slowly poured into a separation device with super hydrophobic cotton fabric as separation membrane ( Figure 7 In (a), due to the superhydrophobicity and superoleophilicity of the coated fabric, water remains on the fabric, while ethylene dichloride can penetrate the fabric to achieve separation.

[0137] When separating a mixture of light oil represented by n-hexane and water (water removal model), the super-hydrophobic cotton fabric can be treated with an acidic aqueous solution (pH = 2) in advance. After the treatment, the mixture of n-hexane and water is slowly poured into a separation device with a super-hydrophobic cotton fabric as a separation membrane. Water can quickly pass through the super-hydrophobic cotton fabric while oil cannot pass through the super-hydrophobic cotton fabric, thereby achieving the separation of the light oil / water mixture ( Figure 7 (b)

[0138] like Figure 7 As shown in Figures c and d, even after five cycles, the oil removal and water removal models maintained excellent separation efficiencies of approximately 97.4 ± 0.2% and 97.8 ± 0.3%, respectively. Although the permeate fluxes decreased slightly compared to the initial levels, they were still high, at 13981.53 ± 1346.84 and 11572.90 ± 466.46 L·m, respectively. -2 ·h -1 .

[0139] In summary, the hydrophobicity of the super-hydrophobic cotton fabric prepared by the present invention decreases with the increase of the number of frictions, the number of tape strippings and the ultrasonic test time, but the super-hydrophobicity is not lost after 700 Martindale friction tests, 100 tape tests and 6 hours of ultrasound, respectively; only the strong alkali solution has a certain effect on the super-hydrophobicity of the super-hydrophobic cotton fabric, the strong acid solution and the organic solvent have no effect on the super-hydrophobicity of the super-hydrophobic cotton fabric, and the long-term heat treatment has no effect on the super-hydrophobic effect of the super-hydrophobic cotton fabric.

[0140] Although the present invention has been disclosed as above in the form of a preferred embodiment, it is not intended to limit the present invention. Anyone familiar with this technology can make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, the scope of protection of the present invention should be based on the definition of the claims.

Claims

1. A method for preparing a pH-responsive polymer solution, characterized in that: The steps include: Dissolving bis(3-aminopropyl)-terminated poly(dimethylsiloxane) and diisocyanate compounds in an organic solvent for prepolymerization, and then slowly adding a polyamino compound containing a tertiary amino group to carry out addition polymerization to obtain a pH-responsive polymer solution; Wherein, the polyamino compound containing tertiary amino group is one or two of tris(2-aminoethyl)amine and laurylamine dipropylene diamine; The molar ratio of the bis(3-aminopropyl)-terminated poly(dimethylsiloxane), the diisocyanate compound and the polyamino compound containing tertiary amino groups is 1-4:2-14:2-10.

2. The pH responsive polymer solution prepared by the method according to claim 1.

3. The pH responsive polymer solution according to claim 2, characterized in that The mass fraction of the pH responsive polymer in the pH responsive polymer solution is 5-25%.

4. A method for preparing a pH-responsive and self-healing superhydrophobic material, characterized in that: The steps include: Hydrophobic nanoparticles are added to the pH-responsive polymer solution of claim 2, and mixed evenly to obtain a mixed solution; then, the cellulose fiber material is immersed in the mixed solution, taken out, and solidified to obtain a pH-responsive and self-repairing superhydrophobic material.

5. The method according to claim 4, characterized in that The hydrophobic nanoparticles are one or more of titanium dioxide, silicon dioxide and carbon black nanoparticles; and the particle size is 1-200 nm.

6. The pH-responsive and self-repairing super-hydrophobic material prepared by the method described in claim 4 or 5.

7. Application of the pH-responsive polymer solution of claim 2 and the pH-responsive and self-healing superhydrophobic material of claim 6 in the fields of antifouling, self-cleaning, anti-icing, anti-corrosion or water-oil separation.

8. An oil-water separation method, characterized in that: It adopts the pH-responsive and self-repairing superhydrophobic material described in claim 6.

9. A method for improving the pH response, superhydrophobicity and self-repairing properties of cotton fabrics, characterized in that: It adopts the pH-responsive and self-repairing superhydrophobic material described in claim 6.

10. A method for quickly achieving reversible switching of super-hydrophobic-hydrophilic-super-hydrophobic properties on the surface of a cotton fabric, characterized in that: It adopts the pH-responsive and self-repairing superhydrophobic material described in claim 6.

Citation Information

Patent Citations

  • Preparation method of pH-responsive super-hydrophobic material

    CN112981973A

  • Preparation method of pH-responsive super-hydrophobic-hydrophilic reversible conversion material surface

    CN113463402A

  • PH-responsive water-based organic silicon polyurethane emulsion as well as preparation method and application thereof

    CN116948129A

  • Polyurethane coating with hydrophobicity, ice hydrophobicity and self-healing capacity as well as preparation method and application of polyurethane coating

    CN117089271A

  • Self-healing, self-cleaning omniphobic composition, related articles and related methods

    US20220041787A1